Factors Affecting Indonesian Public Company Disclosure Of CSR Activities - Glennisa, Cynthia; Martusa, Riki; Meythi Meythi (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
This study aims to examine the size of the board of commissioners, the size of the audit committee, and the reputation of the CPA firm on the disclosure of the company's Corporate Social Responsibility (CSR) activities. We use a regression model based on secondary data sources. The study's samples used several industry categories listed on the Indonesian Stock Exchange between 2019 and 2021. We will use SPSS software for multiple linear regression data analysis to understand the connection between the three factors and CSR activity disclosure. The results showed that the size of the board of commissioners did not affect the company's CSR activity disclosure. In contrast, the size of the audit committee and CPA firms' reputations affected the company's CSR activity disclosure. This study implies that the CSR of CPA firms depends on two factors: i.e. their reputation and the audit committee size.